Forecasting the effect of water gastric emptying patterns on model drug release in an in vitro glass-bead flow-through system - Felicijan Tjaša; Bogataj Marija (Acta Pharmaceutica)
Oral solid dosage forms are most frequently administered with a glass of water which empties from the stomach relatively fast, but with a certain variability in its emptying kinetics. The purpose of this study was thus to simulate different individual water gastric emptying (GE) patterns in an in vitro glass-bead flow-through dissolution system. Further, the effect of GE on the dissolution of model drugs from immediate-release tablets was assessed by determining the amount of dissolved drug in the samples pumped out of the stomach compartment. Additionally, different HCl solutions were used as dissolution media to assess the effect of the variability of pH of the gastric fluid on the dissolution of three model drugs: paracetamol, diclofenac sodium, and dipyridamole. The difference in fast and slow GE kinetics resulted in different dissolution profiles of paracetamol in all studied media. For diclofenac sodium and dipyridamole tablets, the effect of GE kinetics was well observed only in media, where the solubility was not a limiting factor. Therefore, GE kinetics of co-ingested water influences the drug release from immediate-release tablets, however, in certain cases, other parameters influencing drug dissolution can partly or fully hinder the expression of this effect.